Empowering Arabic Language Teachers through a Community-Based Research (CBR) Approach in Facing Digital Literacy Challenges at Madrasah Aliyah West Pasaman - Rahmawati; Ilya Husna; Zaimatuz Zakiyah; Fitrah Dinanti Massofia; Shofia Na’ilatul Haq (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2026)
One of the benchmarks of 21st century learning success is the use of technology. Therefore, teachers should master the skills necessary to achieve such success. This assistance aims to identify existing problems and offer practical solutions that can be applied by teachers in West Pasaman that are compiled collectively. In this regard, the method used in this assistance is the Community-based Research (CBR) method which allows for cooperation between the service (researcher) and the community in carrying out each stage. The assisted community is a deliberation or Arabic teacher association which will be a model for the development of learning literacy, because it is considered to have the potential for the development of skills and literacy in the 21st century. The collected data was analyzed using Miles and Huberman techniques, namely data reduction, data presentation, and conclusion drawn. The results of the mentoring showed that the main problems of teachers were educational background, competence, literacy, lack of motivation, workload, family conditions, lack of collaboration, no opportunity to participate in training, limited information, and limited class hours. The activities to overcome these problems are holding digital literacy training and workshops, followed by project-based learning, developing a curriculum that inserts 21st century skills, using collaborative platforms, such as Google Classroom, Padlet, and so on, and carrying out skills-based evaluations.